Vitamin and Mineral Supplementation of Children under Current Conditions - Yu.V. Marushko (Zaslavsky O.Yu., 2015)
This paper presents data about the state of vitamin and trace-element supplementation of children from different countries and Ukraine. It was shown that nutrition does not fully satisfy the need for vitamins and trace elements that indicates the need for additional prescription of vitamin mineral complexes.